Is There a "Theology of the Disabled Body"? John Paul II's Theology of the Body on Limit and Sign - Windley, Susan (Journal of disability & religion, 2016)
This essay examines the potential influence of John Paul II's theological anthropology as expressed in the Theology of the Body audiences and associated literature on key issues raised by the contemporary Theology of Disability. Although John Paul II did not directly address the issue of disability in the audiences, he does spend the first half of the audiences elaborating a theology of the sign of the human body, and its import in understanding that we are all called to self-giving relationship. The foci on the ensouled body as sign and the imago Dei best perceived in relationship can both reveal a way of thinking about the meaning of the impaired, ensouled body that honors and frames the experience of unexpected limit and the universal call to holiness.